Simple inheritance, complex regulation: Supergene‐mediated fire ant queen polymorphism. Issue 19 (26th August 2020) - Arsenault, Samuel V.; King, Joanie T.; Kay, Sasha; Lacy, Kip D.; Ross, Kenneth G.; Hunt, Brendan G.
Abstract: The fire ant Solenopsis invicta exists in two alternate social forms: monogyne nests contain a single reproductive queen and polygyne nests contain multiple reproductive queens. This colony‐level social polymorphism corresponds with individual differences in queen physiology, queen dispersal patterns and worker discrimination behaviours, all evidently regulated by an inversion‐based supergene that spans more than 13 Mb of a "social chromosome, " contains over 400 protein‐coding genes and rarely undergoes recombination. The specific mechanisms by which this supergene influences expression of the many distinctive features that characterize the alternate forms remain almost wholly unknown. To advance our understanding of these mechanisms, we explore the effects of social chromosome genotype and natal colony social form on gene expression in queens sampled as they embarked on nuptial flights, using RNA‐sequencing of brains and ovaries. We observe a large effect of natal social form, that is, of the social/developmental environment, on gene expression profiles, with similarly substantial effects of genotype, including: (a) supergene‐associated gene upregulation, (b) allele‐specific expression and (c) pronounced extra‐supergene trans ‐regulatory effects. These findings, along with observed spatial variation in differential and allele‐specific expression within the supergene region, highlight the complex gene regulatory landscape that emerged following divergence of the inversion‐mediated Sb haplotype from its homologue, which presumably largely retained the ancestral gene order. The distinctive supergene‐associated gene expression trajectories we document at the onset of a queen's reproductive life expand the known record of relevant molecular correlates of a complex social polymorphism and point to putative genetic factors underpinning the alternate social syndromes.